The Holocaust and the Nakba : a new grammar of trauma and history - Bashir, Bashir; Goldberg, ʿAmos 1966-; Ḫūrī, Ilyās 1948-; Rose, Jacqueline 1949- (Religion, culture, and public life, 2019)
"This book deals with two very painful and traumatic events in Jewish and Palestinian history...the Holocaust and the Nakba. Both events, which differ in nature and in degree, have had a decisive impact on the subsequent history, consciousness and identities of the two peoples. The Holocaust has become a central component of Jewish identity, particularly since the late 1970s and the 1980s, in Israel and around the world. The Nakba and its persisting consequences have become a crucial part of Palestinian and Arab identities since 1948. For the Palestinians, the Nakba is not merely about their defeat, their ethnic cleansing from Palestine and the loss of their homeland, nor even about having become a people most of whom live as refugees outside their land, and a minority living under occupation in their own land. The Nakba also represents the destruction of hundreds of villages and urban neighborhoods, along with the cultural, economic, political and social fabric of the Palestinian people. It is the violent and irreparable disruption of the modern development of Palestinian culture, society, and national consciousness. It is the ongoing colonization of Palestine that continues to the present through colonial practices and polices like Jewish settlements, illegal land acquisition, and the emptying of villages"...